2018
DOI: 10.1002/anie.201804881
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Fe2+ into Nickel–Iron Layered Double Hydroxide: Local Structure Modulated Water Oxidation Activity

Abstract: Exploring materials with regulated local structures and understanding how the atomic motifs govern the reactivity and durability of catalysts are a critical challenge for designing advanced catalysts. Herein we report the tuning of the local atomic structure of nickel-iron layered double hydroxides (NiFe-LDHs) by partially substituting Ni with Fe to introduce Fe-O-Fe moieties. These Fe -containing NiFe-LDHs exhibit enhanced oxygen evolution reaction (OER) activity with an ultralow overpotential of 195 mV at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
209
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 305 publications
(222 citation statements)
references
References 35 publications
(22 reference statements)
13
209
0
Order By: Relevance
“…Next, we engineered the active Fe sites through a facile acid treatment. First, following a well‐developed co‐precipitation synthetic approach, NiFe LDH catalyst was obtained through the hydrolysis of iron nitrates and nickel nitrates in water. Then, the obtained dried catalyst was subjected to the same amount of deionized water containing different volumes (25, 50, 100 μL) of 1 m nitric acid at room temperature for 30 min, which gave rise to catalysts NiFe LDH‐A25, NiFe LDH‐A50, and NiFe LDH‐A100, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we engineered the active Fe sites through a facile acid treatment. First, following a well‐developed co‐precipitation synthetic approach, NiFe LDH catalyst was obtained through the hydrolysis of iron nitrates and nickel nitrates in water. Then, the obtained dried catalyst was subjected to the same amount of deionized water containing different volumes (25, 50, 100 μL) of 1 m nitric acid at room temperature for 30 min, which gave rise to catalysts NiFe LDH‐A25, NiFe LDH‐A50, and NiFe LDH‐A100, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…While the Mn 2p region for the FeCoMn/NF can be fitted into six peaks at 640.6 eV, 642.0 eV and 643.4 eV for Mn 2p 3/2 as well as 652.2 eV, 653.7 eV and 655.6 eV for Mn 2p1/2 (Figure b), implying the co‐existence of Mn 2+ , Mn 3+ and Mn 4+ . The binding energies (BEs) of Fe 3+ are probed at 711.2 eV and 724.7 eV in the FeCo(Mn)−O/NF (Figure c) . Co 2p spectra of FeCo(Mn)−O/NF are deconvoluted into three groups of characteristic signals at 780.8 eV, 782.7 eV and 786.7 eV (satellite peak) for 2p3/2 as well as 796.8 eV, 798.1 eV and 803.0 eV (satellite peak) for 2p1/2 (Figure d), suggesting the coexistence of Co 3+ and Co 2+ .…”
Section: Figurementioning
confidence: 95%
“…[32,33] The binding energies (BEs) of Fe 3 + are probed at 711.2 eV and 724.7 eV in the FeCo(Mn)À O/NF (Figure 3c). [34,35] Co 2p spectra of FeCo(Mn)À O/NF are deconvoluted into three groups of characteristic signals at 780.8 eV, 782.7 eV and 786.7 eV (satellite peak) for 2p3/2 as well as 796.8 eV, 798.1 eV and 803.0 eV (satellite peak) for 2p1/2 (Figure 3d), suggesting the coexistence of Co 3 + and Co 2 + . [36,37] The O 1s region of FeCo (Mn)À O/NF exhibits four BEs at 529.9 eV, 530.9 eV, 531.5 eV and 532.0 eV (Figure 3e), which can be assigned respectively to lattice oxygen (O lat ), defective oxygen (O def ), metal hydroxide and absorbed water.…”
mentioning
confidence: 99%
“…[5] Previous dedications in designing efficient OER catalysts include noble-metal oxides, [6] perovskites, [7] transition-metal oxides, [8] sulfides [9] and (oxy)hydroxides. [10] Among the various OER catalysts developed so far, NiFeh ydroxide (NiFe-LDH) is apotential species with promising activity, [11] yet its catalytic activity is still badly limited by the weak oxygenated intermediates adsorption. Recent theoretical studies by Nørskov [12] reported the vital role of Fe in (Ni,Fe)OOH and Goddard [13] stated that Fe in NiFe-LDH can benefit the OC radical formation and Ni facilitates the OÀOcoupling, but the weak adsorption of NiFe-LDH to the oxygenated intermediates (specially *OH) is potentially the highest energyconsuming step.T ofurther improve the catalytic performance of NiFe-LDH in OER, the binding of oxygenated intermediates has to be strengthened.…”
mentioning
confidence: 99%